SEAGRASS CONSERVATION EDUCATION BASED ON COASTAL CHILDREN EMPOWERMENT IN TELUK BAKAU, BINTAN REGENCY - Samnuzulsari, Tri; Pranata, Yogi; Bachtiar, Aidin Fitrah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This research focuses on educating coastal children in Teluk Bakau, Bintan Regency, about the importance of seagrass ecosystems and the threats they face. The seagrass ecosystem has an important role in maintaining the balance of marine ecosystems, including as a habitat for various marine species and supporting the global carbon cycle. However, seagrass meadows are threatened by uncontrolled human activities, pollution, and climate change. Through descriptive methods and a community service approach, this research succeeded in increasing the knowledge of coastal children, as evidenced by the significant increase in participants' post-test scores after participating in the educational program. The majority of participants experienced an increase in knowledge, with the average score increasing from 5.1 on the pre-test to 7.45 on the post-test. These results show the effectiveness of the program in increasing environmental awareness among coastal children. However, there was variation in the level of knowledge improvement among participants, indicating the need for more adaptive and interactive learning methods. The success of this program emphasizes the importance of environmental education from an early age in forming a generation that cares and plays an active role in ecosystem conservation, especially seagrass beds in the coastal area of ​​Teluk Bakau.